Unspoken Meaning: A Study of Flouting Conversational Maxims in 500 days of Summer - Valentina Ni Kadek; Ni Wayan Suastini (Universitas Islam Negeri Palopo, 2025)
This study explores how the flouting of conversational maxims in 500 Days of Summer impacts character interactions and relationship dynamics. The primary objective is to understand how ineffective communication shapes emotional connections in the narrative. Through qualitative analysis, we identified and categorized instances of maxim flouting, revealing the following frequencies and percentages: flouting the maxim of quantity (8 instances, 24.2%), flouting the maxim of quality (8 instances, 24.2%), flouting the maxim of relevance (8 instances, 24.2%), and flouting the maxim of manner (9 instances, 27.3%). Notably, the maxim of manner was the most frequently flouted, indicating that characters often communicate with ambiguity that adds emotional complexity. In contrast, the maxims of quantity, quality, and relevance were least commonly flouted, suggesting that while miscommunication occurs, dialogue generally maintains a balance between clarity and emotional expression. These findings underscore the critical role of effective communication in fostering intimacy and understanding in romantic relationships. Additionally, the study acknowledges the limitations of focusing on a limited number of scenes, which may not capture the full spectrum of communication dynamics within the film. Future research could expand on these insights by examining other conversational maxims across different media and investigating how cultural contexts influence communication styles.